ISLAM DAN MENEPAUSE: - Mustaring Mustaring (DIKTUM: Jurnal Syariah dan Hukum, 2010)
This article presents the significance of Islamic counseling for menopausal women. Using multiple approaches, this study reveals that menopause is a biological process that will be experienced by all living creatures, including human beings, especially women. In this menopause phase, there will be some changes in all human parts. All human parts will gradually undergo structural and functional decline, and eventually will be dysfunctional. In Islamic perspective, men and women have equal status. The difference is only in biological aspect and in their role in social life. Therefore, the psychological problems for menopausal women needs counseling based on religious teachings.